Peer Effects in the Adoption of a Youth Employment Subsidy - Mora-García, Claudio A.; Rau, Tomás (The Review of Economics and Statistics, 2023)
Abstract This paper studies the effects of peers on the adoption of a Youth Employment Subsidy in Chile since its inception. We examine the effects that former classmates' and coworkers' adoption have on one's adoption. Identification comes from discontinuities in the assignment rule that allow us to construct valid instrumental variables for peers' adoption. Using a comprehensive set of administrative records, we find that classmates and especially coworkers play significant roles in the adoption of the subsidy. Peer effects are determined during the early stages of the program's implementation and vary by network characteristics and the strength of network ties.